Peculiarities of Chronology in Christopher Buckley’s Novel They Eat Puppies? Don’t They (Texas Journal of Philology, Culture and History, 2022)
In this article the problem of chronology in political satirical novel is investigated. In such novels the category of time is generally being of secondary importance as the ultimate goal of writer is to reveal the mechanisms of political system or universal truth hidden be politicians. However, in the novel They eat puppies, don’t they chronology also indicates the pace of the plot. The category of time is presented in various markers, making this novel topical for a research.